Identification and genomic characterization of a novel porcine parvovirus in China - Guo, Yajing; Yan, Guangzhi; Chen, Shengnan; Han, Hui; Li, Jiaming; Zhang, Haoquan; Luo, Shicheng; Liu, Mingjie; Wu, Qingqing; Li, Qingxian; Tu, Changchun; Huang, Liangzong; et al. (Frontiers in Veterinary Science, 2022)
Porcine parvoviruses (PPVs) are a group of small non-enveloped viruses with seven species (porcine parvovirus 1-7, PPV1-7) have been identified. In this study, a novel porcine parvovirus, provisionally named porcine parvovirus 8 (PPV8), was initially identified via high-throughput sequencing (HTS) in porcine reproductive and respiratory syndrome virus-positive samples collected from swine herds in Guangdong province, 2021. The nearly full-length genome of PPV8 strain GDJM2021 is 4380 nucleotides in length with two overlapping open ORFs encoding NS1 and VP1 respectively. Sequence analysis indicated that PPV8 shared 16.23%-44.18% sequence identity at the genomic levels to PPV1-7 with the relatively highest homology to PPV1. PPV8-GDJM2021 shared 31.86%-32.68% aa sequence identity of NS1 protein with those of PPV1 and porcine bufavirus (PBuV), and formed an independent branch neighboring to those formed by members of the genus Protoparvovirus. Of the 211 clinical samples collected from 1990-2021, 37 samples (17.5%) distributed over 12 regions in China were positive for PPV8 with time spanning 24 years (1998-2021). To our knowledge, this is the first report on the genomic characterization of the novel PPV8 and its epidemiological situations in China.